ANALISIS KARAKTERISTIK DAN PERILAKU ANAK LAMBAN BELAJAR DI di SEKOLAH DASAR : Lamban belajar - NAINGGOLAN, POPPHY; Nainggolan, Popphy Yolanda; Fildawati, Evi Fildawati; Ginting, Isaura Regina br; Anabel, Maria; Syam, Herina Maulini; Simanjuntak, Jesika; Nafisa, Shakira (PT. Marosk Zada Cemerlang, 2024)
This research aims to analyze the characteristics and behavior of slow learners in elementary school. Children who are slow learners, or slow learners, often show low academic achievement and have difficulty understanding subject matter. The main characteristics of slow learners include the inability to focus, difficulty in completing assignments on time, and limitations in cognitive and social abilities. This research uses observation and interview methods to collect data from students and teachers in several elementary schools. The research results show that slow learners often behave differently compared to their peers. They tend to be inactive in discussions, have difficulty expressing ideas, and prefer to play alone. Apart from that, they also have difficulty remembering information and understanding verbal instructions. Factors that influence the slow learning process include conditions before birth, at birth, as well as environmental and social factors .